We need to collect the d terms on one side and the constants on the other. Remember that when you move something from one side to the other, you have to change it from positive to negative or from negative to positive:
2d + 36 = -3d - 54
=> 2d + 3d = -54 - 36
=> 5d = -90
=> d = -90 / 5
=> d = -18.
2007-01-10 15:55:09
·
answer #1
·
answered by Scarlet Manuka 7
·
2⤊
0⤋
For this one you have to combine like terms. First do the letters. You have to add 3d to each side now the equation is 5d+36=-54. Then you combine the numbers by adding 36 to each side so now the equation is 5d=-90. The last step is -90 divided by 5=-18 so d=-18.
2007-01-11 00:03:17
·
answer #2
·
answered by Al M 1
·
0⤊
0⤋
2d + 36 = -3d - 54
+2d + 36
<-d -18>
2007-01-10 23:56:55
·
answer #3
·
answered by JAMES R 3
·
0⤊
0⤋
2d+36=-3d-54
2d+36+54=-3d-54+54
2d+90=-3d
2d-2d+90=-3d-2d
90=-5d
90/-5=d
-18=d
Just remember what ever you do to one side of the equation you have to to do the other. As long as you keep that in mind you will be ok....Oh and the variable stands alone, the variable stands alone...High ho the math-O the variable stands alone!
2007-01-11 00:05:10
·
answer #4
·
answered by wendy g 3
·
0⤊
0⤋
2d+36=3d-54
-2d from both sides:
36=1d-54
add 54 to both sides:
90=d(answer)
plug in to check answer:
2(90)+36=3(90)-54
180+36=270-54
216=216
2007-01-10 23:59:45
·
answer #5
·
answered by rose a 1
·
0⤊
0⤋
2d + 36 = -3d - 54
2d + 3d = -54 - 36
5d = - 90
d = -90/5 = - 18
2007-01-10 23:57:04
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
2d+36= -3d-54
2d+3d=-54-36
5d=-90;divide both terms by 5
d=-18
2007-01-10 23:57:21
·
answer #7
·
answered by Akoh 2
·
0⤊
0⤋
2d+36 = -3d-54
2d+3d+36-36=-3d-3d-54-36
5d=-90
5d/5=-90/5
d= -18
2007-01-11 00:00:28
·
answer #8
·
answered by mishasma 2
·
0⤊
0⤋
2d+3d=-54-36
or d=-90/5
d= -18
2007-01-10 23:56:51
·
answer #9
·
answered by Abu F 2
·
0⤊
0⤋
add 3d to both sides
5d+36=-54
Subtract 36 from both sides
5d=-90
Divide both sides by 5
d=-18
2007-01-10 23:55:28
·
answer #10
·
answered by Professor Maddie 4
·
2⤊
0⤋